An Analysis of Persuasive Sentence in Tourism Promotion Brochure in North Nias - Hulu, Delan Septiani; Harefa, Afore Tahir; Zega, Riswan; Waruwu, Yaredi (Civiliza Publishing, Indonesia., 2025)
This study aims to analyze the use of persuasive sentences in tourism promotion brochures published by the North Nias Regency Tourism and Culture Office. The focus of this study is to identify the types of persuasive sentences based on Aristotle's rhetorical theory (ethos, pathos, logos, and call to action/CTA) as well as the linguistic elements used to influence potential tourists. The method used is a qualitative approach through document analysis of selected brochures and in-depth interviews with two key informants from the office. The results of the study show that the brochures use more logos sentences (70%) and pathos sentences (27.5%), while ethos sentences are not found at all, and CTA only appears at 2.5%. Of the nine linguistic elements according to Gorys Keraf's theory, only four were found: personification (7.5%), repetition (5%), imperative (2.5%), and hyperbole (2.5%), while other elements such as pronouns, adjectives, assonance, metaphors, and synecdoche did not appear. These findings indicate that the narrative structure in brochures is still intuitive and not yet fully based on a scientific approach. Therefore, this study recommends that the agency improve the balance of persuasive strategies, increase the use of CTAs, and enrich the variety of linguistic elements to make brochures more appealing to readers.